Descriptive Analysis Of Maternal Anxiety Before Sectio Caesaria Surgery - Zuhana, Nina; Prafitri, Lia Dwi; Ersila, Wahyu (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research aims to find out the picture of maternal anxiety before sectio caesarean at Muhammadiyah Pekajangan Islamic Hospital Pekalongan. This research is a quantitative descriptive study using a cross sectional approach. The population in this study was mothers who gave birth in pre-caesarean sections at The Islamic Hospital Muhammadiyah Pekajangan Pekalongan. Sampling technique using quota sampling type, which is 30 respondents who meet inclusion criteria and do not drop out. Data collection using the T-MAS questionnaire (Taylor Anxiety Scale) method of data collection with interviews. The results found that 100% of respondents experienced anxiety and Most (70%) have severe anxiety before SC surgery. It is hoped that health workers especially midwives can provide information and provide positive support that can reduce the anxiety of clients before surgery sectio caesaria